Percutaneous Coronary Intervention (PCI) of Left Main (LM) Stem Disease: Our Experiences in a Tertiary Care Hospital (Bangladesh Heart Journal, 2021)
Background: It is well known that coronary artery bypass graft (CABG) is considered as gold standard treatment of left main (LM) stem disease. Over the years PCI of left main (LM) stem disease, proved its non-inferiority to CABG in treating LM stem diseaseObjectives: Exact data of LM stem PCI and its procedural success, in-hospital, and post-procedural one-year survival outcome in-terms of repeat hospitalization due to re-infarction, LVF and death, in our population not known clearly. Therefore, we have carried out this prospective observational cohort to see the overall outcomes of LM Stem, PCI in our populationMethods and materials: Patients who underwent elective CAG and found LM stem disease and planned for PCI, were enrolled in this non-randomized observational study between November 2013 to September 2019. Total 146 patient (F 29; Male 117) were enrolled in this study.Results: Out of 146 patients, female :19.8% (n=29) vs Male: 80.1% (n=117). Among, these patient females were more obese (BMI: Female 29.8 ± 3.6 vs male 26.8 ± 3.8). Male patients were older than female; Male 59 yrs. vs female 56 yrs. Among the CAD risk factors Hypertension (HTN) 67.8% (n=99), dyslipidemia 56.2% (n=82), Diabetes Mellitus (DM) 51.4% (n=75), smoking 31.5% (n=46), Family history of CAD (FH) 21.2% (n=31). In this study, 19.2%(n=28) patient had CABG in the past. Common Stented territories were ostial LM 6.8%(n=10), shaft of LM 28.8% (n=42), distal LMLAD 47.3% (n=69), distal LM-LCX 15.1% (n=22) and distal LM-RI 2.7% (n=4). Common DES were Everolimus 69.9% (n=102), Sirolimus 12.3% (n=18), Zotarolimus 9.6%(n=14), BMS 4.8% (n=7), Sirolimus with Epithelial Progenitor Cell 3.4% (n=5), and Biolimus 2.1% (n=3). In terms of post procedural dual antiplatelet therapy (DAPT), patients receiving Clopidogrel were 57.5% (n=85), Ticagrelor 28.8% (n=42), and Prasugrel 13.7% (n=20). Total 12 patient died due to acute, sub-acute stent thrombosis or reinfarction with or without arrhythmia. Relook CAG done was only in 14.4% (n=21) patients, Stent patency 80.9% (n=17), significant ISR, later went to CABG 14.3%(n=3) and mild ISR 4.7% (n=1). IVUS guided PCI were done only in 10.9% (n=16) patients. Major adverse cardiac events in terms of periprocedural MI, repeat hospitalization or death were not common in this study.Conclusion: PCI of LM stem disease is one of the important treatment modalities over CABG in our patient population. Very few patients developed re-stenosis, that needs repeat revascularization either by PCI or CABG. Thus, we may conclude, PCI of LM stem disease might be an alternative to CABG and needs comparative multicenter study to justify its superiority outcome in our patient population.Bangladesh Heart Journal 2020; 35(2) : 78-86